Scope of health problems managed by general practitioners in Mali and France: awaiting practice transition in sub-Saharan Africa?. (12th June 2020) - Naville, Raphaël; Subtil, Fabien; Sy, Mansour; Marquis, Michel; Costes, Pierre; Letrilliart, Laurent
Abstract: Background: Minimal data are available on the clinical activity of general practitioners (GPs) in Africa. Objective: To describe the health problems managed by GPs in Mali as compared with France where epidemiological transition is already advanced. Methods: A retrospective, multicenter study, conducted in five Malian Community Health Centers. We compared their consultation data to those of the ECOGEN (Eléments de la COnsultation en médecine GENérale) study conducted in 128 French general practices, after data standardization for age and sex. Results: Malian and French databases included 19 068 and 19 341 consultations, respectively. Patients had an average of 1.2 health problems managed per consultation in Mali, versus 2.2 in France. They were dominated by infections (51.3%) in Mali, including malaria (24.9%), pneumonia (9.0%) and gastrointestinal infections (5.0%). In comparison with French GPs, Malian GPs more frequently managed cardiovascular (20.2% versus 13.5%), respiratory (15.0% versus 12.4%) and digestive (13.3% versus 7.8%) problems, and less frequently musculoskeletal (3.1% versus 12.6%), endocrine/metabolic (1.5% versus 10.7%) and psychological (0.2% versus 8.2%) problems. The main activity performed by French GPs was prevention (11.0%), which was nominal in Mali. Apart from hypertension, which accounted for 18.9% of the health problems managed in Mali, chronic conditions were less often managed by Malian GPs than by French GPs (12.3% versus 39.6%). Conclusions: Africa is currently at the crossroads where chronic conditions carried with the epidemiological transition are progressing, while the burden of communicable diseases is still overwhelming. Along with the enhancing medicalization of primary care in Mali, the transition of practices is just emerging.